RESPONSIBILITAS PT. EKA DURA INDONESIA SEI MANDING RIAU MELALUI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DI KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU - Syadza Qonitha Hazimah; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Under the laws of the Republic of Indonesia Number 40 of 2007 on limited liability company Chapter I Article 1 point 3 States that social and environmental responsibility is a commitment of the company to participate in sustainable economic development in order to improve the quality of life and the environment is beneficial, both for the company itself, the local community as well as society in General. The purpose of this study was to analyse responsibility PT. Eka Dura Indonesia Sei Manding Riau through programs of Corporate Social Responsibility (CSR) in Subdistrict Kunto Darussalam District Rokan Hulu with factors that affected it. CSR concept used is from the aspect of economic responsibility, legal responsibility, ethical responsibility and the responsibility of the diskresi. The data are collected with interviews and analyzed with a qualitative approach.Key words : Economic responsibilities, Legal responsibility, Ethical responsibilities, discretionary responsibilities